Hadis-Hadis tentang Toleransi Beragama dalam Pemahaman dan Pengamalan Siswa SMK Texar Karawang - Annisa Azizah Zakiyyah (Jurnal Penelitian Ilmu Ushuluddin, 2022)
Religious harmony should be realized by mutual respect among fellow religious adherents. The reality that occurs in social life is still found in various cases of intolerance. This is a problem that needs to be solved. Understanding of religious teachings and education is needed to foster harmony. Therefore, this paper discusses the Hadith of the Prophet Muhammad SAW related to the teachings of tolerance by analyzing the hadiths that have the same theme. The method used in this research is a descriptive qualitative method using Living Hadith.  Tolerance emphasizes the attitude of accepting existing differences and responding well in order to maintain peace among others. Islam is a religion that makes tolerance the most important part, this attitude is more widely applied in social interactions as the Prophet Muhammad SAW has described that the Islam that he spread on earth has educated humans to be able to respect each other among fellow believers without hatred and revenge.